Uncovering the act of maternal infanticide from a psychological, political and Jungian perspective - Laufer, Brooke (Routledge, 2025)
"Using a wide range of disciplinary backgrounds, Laufer examines the topic of maternal infanticide through the lens of Jungian theory and presents an integrated and forensic view of this issue as an aggregate of personal and political moments, and as a feminine and feminist outcry urging human evolution. The first part of the book will dissect the identity of the infanticidal mother and the Death Mother archetype, with the author providing firsthand accounts of patients that she has worked with in her professional career. The second part of the book focuses on interpreting that act of maternal infanticide, and these chapters will look to the construct of patriarchal Motherhood as a way of explaining the drive and actions of an infanticidal mother. The third and final section of the book takes the concept of evolution and transmutation a step further and addresses what is required in our modern state for the event of maternal infanticide. This is an important new book for Jungian and analytic clinicians and scholars with an interest in maternal archetypes, as well as psychologists and psychiatrists who specialise in perinatal mental health. It would also be appropriate for forensic psychologists and legal analysts, and academics and clinicians in the fields of women's health and studies"--